KASUS “DESAK MADE DARMAWATI” SEBAGAI REFLEKSI PEMBELAJARAN DALAM MENUMBUHKAN INSAN MODERAT DI INDONESIA - I Dewa Gede Darma Permana; Widya Ayu Candra; Fariz Alexander Lutfhianza (UHN I Gusti Bagus Sugriwa Denpasar, 2024)
Diversity has become a national identity that shows Indonesia's image as a country that respects differences. However, this has also become one of the triggers for conflict of disharmony in the form of cases of religious blasphemy. The “Desak Made Darmawati” case is an example of a religious blasphemy conflict in Indonesia. Through a viral video circulating on social media, he shows himself presenting statements that tend to corner Hindu religious beliefs. Reflecting on these problems, researchers are interested in studying more deeply the implications of the